The Stele of YHWH in Egypt : the Prophecies of Isaiah 18-20 concerning Egypt and Kush. - Balogh, Csaba, 1975- (Oudtestamentische studiën ;, 2011)
This book provides a thorough analysis of Isaiah 18-20, concerned with Egypt and Kush, from the earliest stages to their final contextualisation within the developing corpus of the Isaianic prophecies regarding the nations.